ICU‐free days as a more sensitive primary outcome for clinical trials in critically ill pediatric patients. Issue 4 (7th July 2021) - Cho, Hanjin; Wendelberger, Barbara; Gausche‐Hill, Marianne; Wang, Henry E; Hansen, Matthew; Bosson, Nichole; Lewis, Roger J.
Abstract: Background: Our objective was to assess the association between intensive care unit (ICU)‐free days and patient outcomes in pediatric prehospital care and to evaluate whether ICU‐free days is a more sensitive outcome measure for emergency medical services research in this population. Methods: This study used data from a previous pediatric prehospital trial. The original study enrolled patients ≤12 years of age and compared bag‐valve‐mask‐ventilation (BVM) versus endotracheal intubation (ETI) during prehospital resuscitation. For the current study, we defined ICU‐free days as 30 minus the number of days in the ICU (range, 0–30 days) and assigned 0 ICU‐free days for death within 30 days. We compared ICU‐free days between the original study treatment groups (BVM vs ETI) and with the original trial outcomes of survival to hospital discharge and Pediatric Cerebral Performance Category (PCPC). Results: Median ICU‐free days for the BVM group (n = 404) versus ETI group (n = 416) was not statistically different: 0 ICU‐free days (interquartile range, 0–10) versus 0 (0–0), P = 0.219. Median ICU‐free days were greater for BVM group in 3 subgroups: foreign body aspiration 30 (0–30) versus 0 (0–21), P = 0.028; child maltreatment 0 (0–14.2) versus 0 (0‐0), P = 0.004; and respiratory arrest 25 (1–29) versus 7.5 (0–27.7), P = 0.015. In the original trial, neither survival nor PCPC demonstrated differences in all 3 subgroups—survival was greater with BVM for child maltreatment and respiratory arrest and favorable PCPC was greater with BVM for foreign body aspiration. Overall, in the current study, patients with more ICU‐free days also had greater survival to hospital discharge and more favorable PCPC scores. Conclusions: This initial study of the association between ICU‐free days and patient outcomes during prehospital pediatric resuscitation appears to support the use of ICU‐free days as a clinical endpoint in this population. ICU‐free days may be more sensitive than either mortality or PCPC alone while capturing aspects of both measures.